Dieta de larvas de Salminus brasiliensis (CUVIER, 1816) (CHARACIDAE, SALMININAE) em ambiente natural: relações morfométricas presa x predador - Fucks, Luana Wieczorek (2015)
In order to evaluate the Salminus brasiliensis larval diet in natural environment was analyzed the stomach contents of 200 individuals with standard length ranging between 7.00 to 13.99 millimeters. For that, the food items have been identified, classified and quantified by numeric frequency and occurrence. Were also obtained some morphometric data of both S. brasiliensis larvae and prey captured by them. For the larvae were assessed standard length and size of the mouth, while the prey has been evaluated the maximum height of the body. The material analyzed was collected in the Ilha Grande National Park region in a lotic remaining stretch of the Paraná River, in 18 stations distributed in the main channel, its tributaries and oxbow lakes. The diet of the larvae was predominantly composed of fish larvae, especially of Characiformes and Siluriformes. Cannibalism cases were reported demonstrating that this is a characteristic behavior of the species, and is independent on the availability of other food items. Dorado's larvae show a negative allometric relationship between the proportion size of the upper jaw relative to the standard length, it means, those variables do not grow proportionally throughout the growth. It was observed that there is no selectivity when taking into consideration the height of consumed prey, but their sizes remained within the maximum intake limit, and neither the heights of prey or even the height of the mouth were a factor limiting of intake.